Reviewing the main characteristics of the international forest regime complex and partial explanations for its fragmentation. (1st March 2013) - Giessen, L.
The objectives of this review article are, firstly, to provide an overview of the literature on the main characteristics of what is referred to as the international forest regime and secondly, based on this, to review explanations for fragmentation as its core characteristic. A third aim of the article is to propose fields for future policy-oriented research on global forest governance, the international forest regime and its fragmentation. The article discusses different strands of literature and academic views on the existence and main characteristics of an international forest regime. It regards the recent notion of an international forest regime complex to be a fruitful topic for future research proposals and finds that fragmentation is its analytical core characteristic. In addition, the article reviews partial explanations for the great relevance of fragmentation in the case of the forest regime complex. It discriminates between domestic factors and causes as opposed to those resulting from the international system. Based on the review, the article suggests, lastly, fields for future research on global forest governance, the international forest regime complex and its fragmentation. Les objectifs de cette revue sont d'abord de donner un aperçu de la littérature sur les caractéristiques du régime international des forêts, ensuite d'identifier sur cette base les différentes explications données de la fragmentation qui en est une caractéristique clé, afin de proposer enfin des champs de recherche politique sur la gouvernance globale. Le concept récent de régime international des forêts est perçu comme un thème important pour de nouvelles pistes de recherche, et la fragmentation comme son explication centrale. L'article présente diverses explications partielles justifiant l'importance de cette fragmentation dans le cas du régime international des forêts. Il distingue les déterminants nationaux de ceux résultant du système international. A partir de cette revue, l'article conclut en proposant des champs précis pour les recherches futures sur la gouvernance globale, le régime international des forêts et sa fragmentation.Los objetivos de este artículo de revisión son, primero, brindar una visión general de la bibliografía referida a las principales caracterísiticas de qué se refiere como regimen forestal internacional y segundo, basado en esto, revisar explicaciones de la fragmentación como su característica principal. Un tercer objetivo de este artículo es proponer campos de futura investigación orientados en politicas en gobernabilidad forestal global, el regimen forestal internacional y su fragmentación. El artículo trata distintos hilos de bibliografía y visiones académicas en la existencia y principales características de un regimen forestal internacional. Considera la reciente idea de un complejo regimen forestal internacional como un tema fructífero para distintas propuestas de investigación y encuentra que la fragmentación es la característica analítica central. Además, el artículo revisa explicaciones parciales para la gran relevancia de la fragmentación en el caso del complejo del regimen forestal. Discrimina entre factores y causas domésticas en oposición a los resultantes del sistema internacional. Basado en la revisión, el artículo sugiere, finalmente, campos de futura investigación en gobernalibilidad forestal global, el complejo del regimen forestal internacional y su fragmentación.